Serotonin system is partially involved in immunomodulation of Nile tilapia (Oreochromis niloticus) immune cells - Li, Qi; Jiang, Baijian; Zhang, Zhiqiang; Huang, Yongxiong; Xu, Zhou; Chen, Xinjin; Hou, Xitan; Cai, Jia; Huang, Yu; Jian, Jichang (Frontiers in Immunology, 2022)
Serotonin (5-hydroxytryptamine) is a well-known neurotransmitter affecting emotion, behavior, and cognition. Additionally, numerous immunomodulatory functions of serotonin have been discovered in mammals. However, the regulatory role of the serotonin system in fish immunity remains unclear. In this study, various serotonergic markers in Nile tilapia (Oreochromis niloticus) were identified and characterized. The involvement of the serotonin system during bacterial infection was investigated. Moreover, the expression characteristics and specific functions of serotonergic markers within Nile tilapia immune cells were also assessed. Overall, 22 evolutionarily conserved serotonergic marker genes in Nile tilapia were cloned. Transcription levels of these molecules were most abundant in the brain, and their transcripts were induced during Streptococcus agalactiae infection. Nevertheless, few serotonergic markers exist on Nile tilapia immune cells, and no distinct immunomodulation effect was observed during an immune response. The present study lays a theoretical foundation for further investigation of the immunological mechanisms in fish as well as the evolution of the serotonin system in animals.